THE SITUATION OF USAGE OF ANTIBIOTICS AFTER BASEDOW SURGERY AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objective: Describing the current situation of antibiotic usage after Basedow surgery at Thong Nhat Hospital. Subjects and methods: Retrospective descriptive study on 74 medical records of basedow patients who indicated surgery and had surgery at Thong Nhat hospital from March the 10th, 2021 to June the 10th, 2021. Results: Most of the patients used antibiotics after Basedow surgery with the rate of 64.84%. Antibiotics used after Basedow surgery belonged to two groups of Cefazolin and Ampicillin–Sulbactam with the rate of 54.17% and 45.83% respectively, all patients received injection antibiotics. The rate of patients showing signs of infection was low: 2.70%. The relationship between antibiotic usage and infection rates was unclear. The rate of postoperative infections in patients receiving antibiotics was 2.08% (1/48 patients). The rate of postoperative infections in patients who did not receive antibiotics was 3.84% (1/26 patients). Conclusion: Antibiotics used after Basedow surgery belonged to two groups of Cefazolin and Ampicillin–Sulbactam and were administered by injection. The rate of patients with infection was low.
Keywords: Current situation of antibiotic usage, basedow disease.